2012
DOI: 10.1080/10286020.2011.650885
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ERK1/2-CREB pathway during potentiating synaptic transmission of ( − )clausenamide in rat dentate gyrus

Abstract: To investigate the signal mechanism of (-)clausenamide ((-)-3-hydroxy-5-(hydroxy-phenyl-methyl)-1-methyl-4-phenyl-pyrrolidin-2-one, 1) and for understanding its effect on synaptic transmission, electrophysiological recording was done for basal synaptic transmission determination. Western blot analysis was employed to examine the phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) and cAMP responsive element-binding protein (CREB). Immunohistochemistry and tissue in situ hybridization were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…MAPK activation also upregulates cytokine production by direct phosphorylation of transcription factors such as CREB (cAMP response element binding). CREB has direct effect on structural changes associated with memory formation [136].…”
Section: Mapk Signaling In Diabetes and Admentioning
confidence: 99%
“…MAPK activation also upregulates cytokine production by direct phosphorylation of transcription factors such as CREB (cAMP response element binding). CREB has direct effect on structural changes associated with memory formation [136].…”
Section: Mapk Signaling In Diabetes and Admentioning
confidence: 99%
“…Therefore, synaptic loss was considered as a main cause of dementia, and even some scientists proposed that ‘synaptic loss=AD’. For this reason, the new strategy for treatment of AD is limiting synaptic loss and increasing synaptogenesis 14 , 15 .…”
Section: Nootropic Mechanism Of (–)Claumentioning
confidence: 99%
“…ERK1/2 (or MAPK) pathway forms a parallel branch in insulin signaling and is implicated in multiple forms of synaptic plasticity and cell death (70). Studies on cell cultures observed that MAPK activation led to expression of iNOS, TNFα, IL-1β genes and upregulation of cytokine production (71,72). Kumar et al (73) observed induction of apoptosis in glial cells exposed to high glucose through activation of MAPKs, down regulation of 8-oxoG-DNA glycosylase and increase in 8-hydroxydeoxyguanosine.…”
Section: Introductionmentioning
confidence: 98%